Factors Affecting Work Unit’s Knowledge Processing Style in Alborz Insurance and Its Branch’s in Tehran - mohammad ali Sarlak; siavash Rezaei; hamid reza Shahidi (مدیریت دولتی, 2013)
Intraorganizational units play a critical role in KM processes of acquiring, creating, exchanging, and utilizing knowledge assets. While much attention has been directed to effective knowledge strategies forsupporting organizational KM processes, there is a lack of insightful research on knowledge strategy and its implementation at the work-unit level. This study examines two types of work unit knowledge processing styles (codification g styles (codification and personalization) and explores the re relationship between the critical determinants (task, organization culture ,and technology)and knowledge processing styles. The results showed that information technology and task analyzability were significantly associated with codification, whereas autonomy and task interdependence were strongly related to personalization. interestingly, task variety and solidarity were not associated with any KP styles. The findings from this study suggest that the unit’s organizational variables should harmonize appropriately with its knowledge processing styles. This research is functional as the view point of purpose and it is descriptive and measurable in the point of method.